2018
DOI: 10.4103/jmh.jmh_77_17
|View full text |Cite
|
Sign up to set email alerts
|

Association of dyslipidemia, increased insulin resistance, and serum CA 15-3 with increased risk of breast cancer in urban areas of North and Central India

Abstract: Objective:This study aims to determine the association of dyslipidemia and increased insulin resistance (IR) with increased breast cancer (BC) risk.Materials and Methods:The study group comprised 110 premenopausal and 143 postmenopausal, untreated female BC patients in the age range of 29–72 years. Control group consisted of 117 premenopausal and 141 postmenopausal healthy females in the age range of 23–75. Approximately 8-ml blood samples were drawn to measure various biochemical parameters. Serum glucose, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Namely, improved hepatic function following SVR resulted in improved IR. On the other hand, TC levels usually positively correlate with HOMA-IR [ 41 , 42 ]. However, among SVR patients, TC levels and HOMA-IR were negatively associated with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, improved hepatic function following SVR resulted in improved IR. On the other hand, TC levels usually positively correlate with HOMA-IR [ 41 , 42 ]. However, among SVR patients, TC levels and HOMA-IR were negatively associated with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies conducted in Iraq and North and central India meet with our study findings. [26][27][28] The reason for high serum TC in women with malignant breast tumor can be due to high cholesterol metabolites, 27-hydroxycholesterol, that function as estrogen and increase proliferation of estrogen receptor-positive breast cancer cells. 29 On contrary, studies conducted in Morocco and India showed no statistically significant difference in mean serum TC level between malignant breast tumor and control groups.…”
mentioning
confidence: 99%
“…Kachhawa et al studied the risk of breast cancer-related metabolic indicators in pre- and postmenopausal women in India, and the results showed that the insulin level and HOMA-IR were positively correlated with the risk of breast cancer regardless of the menopausal status. 40 The research was conducted in an Asian population, and the results were more consistent with the Asian population. Our study suggests that metformin improved insulin resistance and prevented the occurrence of breast cancer.…”
Section: Discussionmentioning
confidence: 71%